A autonomia dos sujeitos do campo: métodos e identidades - BENTES, Haroldo de Vasconcelos (Universidade Federal do Pará, 2021)
The article discusses the autonomy of the subjects of the field, under the aegis of Field Education, regarding their protagonisms and identities whether in the School or outside it. The objective is to signal the need to focus efforts towards the existential valorization of these men and women and their productions in space and time, in a strategic way, broadening the legitimate, global-local dialogue and vice versa. In the line of argument, two questions: on the assumptions of autonomy and legitimacy, temporality of knowledge, collective memory, and its specificities? And the importance of the global-local relationship in the existence of those, at the confluence of the paradigm of scientificity and connections with technological advances? The theoretical and methodological foundation aligns the presuppositions of the dialectic, scientificity and Scientific Initiation. In the conclusions: the subjects of the field need to be treated as political agents in the analytical process of reality; Dialogue with connections between local and global, scientificity and technologies as recognized and validated knowledge; The methodological, political and epistemic make of the teacher promoting new possibilities in adult learning; Scientific initiation as a method that broadens and deepens the vision of reality.